Disaster management and faith-based organizations: An Islamic perspective - Bouafia, Bouafia; Zahari, Rustam Khairi (OMICS International, 2017)
Regardless their complexity which overwhelms the capacity of the affecting community to cope with, disasters are increasingly recognizing the necessity of an ultimate response drawing on an extensive variety of skills and manpower. Disaster management requires collaboration between various serving agencies including government, private sector, local communities and faith-based organizations due to the limited available resources. The purpose of this paper is to discuss the participation of faith- based organization in reducing the impacts during disaster situations. The paper therefore, focuses on the Islamic teachings in disaster management through a comprehensive review of the available literature. The paper includes an overview of disaster management, act of God, and view of Islam on disaster management, and faith-based organizations and their contribution in disaster management. It has been found that Islamic based organizations usually have advantage and great potential in terms of cultural acceptance to offer immediate assistance in disaster events and to involve in long-time recovery operations when outside agencies return back home.